Aorto-carotid bypass for orthostatic mediated hypoperfusion transient ischaemic attacks: A case report. (April 2021) - Tesar, Joshua; Favot, Danella; Williams, Livia; Tesar, Peter
Highlights: Orthostatic mediated hypoperfusion transient ischaemic attack is a rare phenomenon. Aorto-carotid bypass is an uncommon procedure usually performed in the setting of dissections and vasculitis affecting the supra-aortic branch vessels. Aorto-carotid bypass can be considered in patients with symptomatic atherosclerotic disease of the supra-aortic branch vessels. Abstract: Introduction and importance: Aorto-carotid bypass is a rare procedure. It is reported to be performed for management of cerebral malperfusion in the setting of supra-aortic branch vessel disease. Malperfusion requiring a bypass is largely secondary to dissection or vasculitis. Atherosclerotic disease of the supra-aortic branch vessels is commonly managed via an endovascular approach. We report a rare and atypical presentation of cerebral malperfusion in the setting of atherosclerotic disease of the innominate and carotid arteries managed with an aorto-carotid bypass graft. Case presentation: A case report of an 80-year-old female presenting with orthostatic mediated hypoperfusion transient ischaemic attacks with episodes of limb shaking and unilateral weakness with postural changes. The malperfusion was in the setting of severe atherosclerotic disease of the innominate and carotid arteries. Clinical discussion and conclusion: Our patient was not amendable to endovascular intervention or a less invasive open approach. The patient underwent an aorto-carotid bypass graft with complete resolution of symptoms. This case highlights a rare manifestation of orthostatic mediated cerebral malperfusion and a successful novel treatment method.